2018
DOI: 10.1038/s41420-018-0119-5
|View full text |Cite
|
Sign up to set email alerts
|

Sarm1 induction and accompanying inflammatory response mediates age-dependent susceptibility to rotenone-induced neurotoxicity

Abstract: Aging is a complex biological process and environmental risk factors like pesticide exposure have been implicated in the increased incidence of age-related neurodegenerative diseases like Parkinson’s disease (PD) but the etiology remains unknown. There is also lack of a proper animal model system to study the progressive effect of these environmental toxins on age-associated neurodegeneration. In this study, we established a drosophila model of aging to study the age-dependent vulnerability to the environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 33 publications
3
30
0
Order By: Relevance
“…Perhaps not surprisingly, we found that in organotypic cultures, susceptibility of DN to AMPA-mediated excitotoxicity increases with age and differentiation status, such that the more complex, larger DN that become more common as the tissue matures, are much more susceptible ( Fig 3 , panel A) than the embryonic-appearing, small and round neurons more common earlier in development ( Fig 3 , panel B). This is consistent with observations where age plays a determining role in the increased susceptibility of DN to chronic rotenone exposure that is accompanied by severe locomotor deficits and decreased lifespan [ 37 ]. Overall, AMPA did not induce cell death in DN at 8 days in vitro, but toxicity became apparent at 15 DIV and most intense at 22 DIV.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Perhaps not surprisingly, we found that in organotypic cultures, susceptibility of DN to AMPA-mediated excitotoxicity increases with age and differentiation status, such that the more complex, larger DN that become more common as the tissue matures, are much more susceptible ( Fig 3 , panel A) than the embryonic-appearing, small and round neurons more common earlier in development ( Fig 3 , panel B). This is consistent with observations where age plays a determining role in the increased susceptibility of DN to chronic rotenone exposure that is accompanied by severe locomotor deficits and decreased lifespan [ 37 ]. Overall, AMPA did not induce cell death in DN at 8 days in vitro, but toxicity became apparent at 15 DIV and most intense at 22 DIV.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the natural molecular target for neuroprotection in a more intact system is the SK3 channel. Our data is also consistent with the neuroprotective effect of SK channel activation in cultured human postmitotic dopaminergic neurons in vitro following rotenone treatment; indeed, sub-lethal concentrations of rotenone are significantly more toxic to DN and cause more motor impairment in older when compared to younger drosophila flies [37]. Additionally susceptibility of differentiated DN from the human neuroblastoma cell line SH-SY5Y is also increased by time in vitro [37].…”
Section: Plos Onesupporting
confidence: 87%
“…3). This is consistent with observations in other models, including susceptibility to rotenone-induced toxicity (Sur et al, 2018). Overall, AMPA did not induce cell death in DN at 8 days in vitro, but toxicity became apparent at 15 DIV and most intense at 22 DIV.…”
Section: Discussionsupporting
confidence: 91%
“…There are no homologs of CD38 present in the genomes of the aging models Drosophila or C. elegans , but both genomes encode homologs of PARP and SARM1 [38]. Expression of the Drosophila homolog of SARM1 increased during aging or mitochondrial ETC inhibition and was shown to play a role in inducing a pro-inflammatory state [39]. NADP + phosphatase activities, resulting in the degradation of NADP + to NAD + , have also been observed in rat liver mitochondrial and Golgi extracts [40,41], but the proteins responsible these activities or any aging-related changes in enzyme activity levels have yet to be identified.…”
Section: Loss Of Nad+ As a Major Cause For Loss Of Nadph With Agingmentioning
confidence: 99%